Fully integrated CMOS fractional-N frequency divider for wide-band mobile applications with spurs reduction - Boon, Chirn Chye (2009)
A spurs reduction fractional-N frequency divider with a frequency range which is 3.5 times larger than that of a conventional fractional-N divider is presented in this paper. A 1.2-GHz quadrature voltage-controlled oscillator (VCO) is designed as the input source of the frequency divider. The circuit was fabricated using the 0.25-μm CMOS technology. The power consumption of the frequency divider and the quadrature VCO are 3 and 6 mW, respectively, at a 2-V supply.